Genetic testing of ocular manifestations of proliferative syndrome to provide pathophysiology-oriented treatment - M.E. Weener; N.A. Bakunina; J.M. Salmasi; G.V. Poryadin; D. Barh; Yu.D. Kuznetsova; L.M. Balashova (РМЖ "Клиническая офтальмология", 2022)
M.E. Weener1, N.A. Bakunina2,3, J.M. Salmasi4, G.V. Poryadin4, D. Barh1, Yu.D. Kuznetsova2, L.M. Balashova2,4 1LLC "Oftalmic", Moscow, Russian Federation 2Non-profit partnership "International Scientific and Practical Center for the Proliferation of Tis-sues of Russia", Moscow, Russian Federation 3N.I. Pirogov City Clinical Hospital No. 1, Moscow, Russian Federation 4Pirogov Russian National Research Medical University, Moscow, Russian Federation Background: uncontrolled cell proliferation of the ocular blood network is one of the leading causes of blindness and low vision worldwide. We summarize relevant published data and our 5-year experience in searching treatment tools for excessive non-productive proliferation. Aim: to describe genetic patterns in patients with ocular blood network proliferation for predicting disease course and selecting adequate treatment. Patients and Methods: 1210 patients with proliferative ocular disorders, retinopathy of prematurity, and diabetes were enrolled. Patients were divided into three groups: (1) monogenic disorders, (2) proliferative vitreoretinopathy and diabetes mellitus, (3) retinopathy of prematurity. Follow-up was 6 to 36 months. Laboratory, genetic, and relevant clinical tests were pursued in all patients. Results: proprietary approach of bioinformatic analysis of whole exome/whole genome sequencing data allows for specifying the proliferative process’s prognosis and severity given clinical and genetic findings. This approach includes the analysis of gene mutations directly or indirectly involved in angiogenesis and key signaling pathways. The analysis of mutation identified in group 2 revealed 509C>T TGFB1 gene polymorphism in two patients and c.3174G>A IGF1R gene polymorphism in three patients. In group 3, the most common VEGFA gene polymorphisms were +13553C>T, -634G>C, +405G>C (rs2010963), and -460C>T (rs833061). Conclusion: specifying the prognosis of the course and severity of proliferative ocular disorders pathogenically-oriented targeted treatment requires specialized genetic testing using an improved data analysis approach. Keywords: proliferative syndrome, diabetes, retinopathy of prematurity, VEGFA, TGFB1, IGF1R, Stickler syndrome, Wagner syndrome, Wolframe syndrome, Marshall syndrome, Norrie disease, Coats disease, retinoschisis. For citation: Weener M.E., Bakunina N.A., Salmasi J.M. et al. Genetic testing of ocular manifestations of proliferative syndrome to provide pathophysiology-oriented treatment. Russian Journal of Clinical Ophthalmology. 2022;22(1):16–22 (in Russ.). DOI: 10.32364/2311-7729-2022-22-1-16-22.